THE ANALYSIS OF EXPERIENTIAL LEARNING ACTIVITIES WITHIN THE MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) PROGRAM ON THE ACADEMIC MOTIVATION OF HIGHER EDUCATION STUDENTS - Utami, Novia; Sitanggang, Marsiana Luciana (Jurnal Mebis, 2024)
This research aims to evaluate the influence of Experiential Learning activities within the context of Merdeka Belajar Kampus Merdeka (MBKM) on the academic motivation of higher education students. Academic motivation is considered a crucial factor in shaping students' academic success, and MBKM's experiential learning is expected to boost learning enthusiasm, skill development, and enhancement of soft and hard skills. The research findings indicate that most students feel motivated and more enthusiastic in attending lectures, with a tendency to increase interest in seeking further knowledge. Additionally, the MBKM program is perceived to enhance the quality of education in higher education institutions, engaging students in academic projects and assignments that support developing soft and hard skills. However, some respondent’s express hesitancy regarding the encouragement to pursue academic ambitions.